Strategi Marketing Mix dalam Upaya Meningkatkan Jumlah Peserta didik Baru dalam Lembaga Pendidikan Islam Swasta - Kunta, Ittaqillah Haitsuma; Muslim, Bukhori; Hefniy (NAAFI: JURNAL ILMIAH MAHASISWA, 2025)
This study aims to analyze marketing mix strategies in increasing the number of new students in private Islamic educational institutions, with a case study at SMA Zainul Hasan Genggong, Probolinggo, East Java. The phenomenon of declining interest in private Islamic schools amid increasingly fierce competition among educational institutions is the background for the importance of this study. The research was conducted to determine how the four elements of the marketing mix—product, price, promotion, and place—are managed within the context of a boarding school-based institution, as well as the challenges and opportunities encountered in their implementation. The research method used was descriptive qualitative with a case study approach. Data collection techniques included in-depth interviews, participatory observation, and documentation, with primary informants including the school principal, promotion staff, senior teachers, and parents. The research findings indicate that the product element has strengths in terms of Islamic curriculum and tahfidz programs, but it has not been packaged in a systematic promotional narrative. The price element is flexible but lacks transparency in its communication to the public. Promotional strategies still predominantly rely on conventional methods and have not fully leveraged social media or digital channels. Meanwhile, the distribution element does not provide adequate online information access, particularly for prospective students from outside the region. The conclusion of this study emphasizes that the marketing mix strategy at SMA Zainul Hasan Genggong needs to be strengthened through a more open, technology-based, and participatory communication approach to enhance the appeal and competitiveness of private Islamic educational institutions in the digital era.